Financial market integration under EMU - Tullio Jappelli; Marco Pagano (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
The single most important policy-induced innovation in the international financial system since the collapse of the Bretton-Woods regime is the institution of the European Monetary Union. This paper provides an account of how the process of financial integration has promoted financial development in the euro area. It starts by defining financial integration and how to measure it, analyzes the barriers that can prevent it and the effects of their removal on financial markets, and assesses whether the euro area has actually become more integrated. It then explores to which extent these changes in financial markets have influenced the performance of the euro-area economy, that is, its growth and investment, as well as its ability to adjust to shocks and to allow risk-sharing. The paper concludes analyzing further steps that are required to consolidate financial integration and enhance the future stability of financial markets.
urn:nbn:de:hebis:30-60370
Keywords: G15; G18; 330; Financial Market Integration; Financial Regulation; EMU; Finanzmarkt; Marktintegration; Europäische Wirtschafts- und Währungsunion; EU-Staaten